Sustainable aviation fuels (SAF) production. process and techno-economic assessment modelling of gas fermentation with SCWG heat integration - Agbo, Simon (2024)
This dissertation investigates the potential of producing sustainable aviation fuel (SAF) through the integration of aerobic gas fermentation and supercritical water gasification of lignin-content, aiming to address increasing environmental challenges and energy supply uncertainties in the aviation industry. The industry currently accounts for 2% of global CO2 emissions, a figure projected to rise due to increasing air traffic. Fuel makes up about 23% of operating costs, highlighting the need for an economically viable, environmentally friendly solution.